Repair of bone defects using adipose-derived stem cells combined with alpha-tricalcium phosphate and gelatin sponge scaffolds in a rat model - CORSETTI, Adriana; BAHUSCHEWSKYJ, Claudia; PONZONI, Deise; LANGIE, Renan; SANTOS, Luis Alberto dos; CAMASSOLA, Melissa; NARDI, Nance Beyer; PURICELLI, Edela (Journal of Applied Oral Science, 2017)
Objectives This study aimed to evaluate the potential of adipose-derived stem cells (ASCs) combined with a modified α-tricalcium phosphate (α-TCP) or gelatin sponge (GS) scaffolds for bone healing in a rat model. Material and Methods Bone defects were surgically created in the femur of adult SHR rats and filled with the scaffolds, empty or combined with ASCs. The results were analyzed by histology and histomorphometry on days seven, 14, 30, and 60. Results Significantly increased bone repair was observed on days seven and 60 in animals treated with α-TCP/ASCs, and on day 14 in the group treated with GS/ASCs, when compared with the groups treated with the biomaterials alone. Intense fibroplasia was observed in the group treated with GS alone, on days 14 and 30. Conclusions Our results showed that the use of ASCs combined with α-TCP or GS scaffolds resulted in increased bone repair. The higher efficacy of the α-TCP scaffold suggests osteoconductive property that results in a biological support to the cells, whereas the GS scaffold functions just as a carrier. These results confirm the potential of ASCs in accelerating bone repair in in vivo experimental rat models. These results suggest a new alternative for treating bone defects.